Dataset: Ghrelin antagonist overrides the mRNA expression of NPY in hypothalamus in feed restricted ewes - Carranza Martín, Ana Cristina (2020)
A negative energy balance (NEB) is detrimental to reproduction in animals. A suggested link between NEB and reproductive failure is the gastrointestinal hormone ghrelin, because of the association between ghrelin and the hypothalamo-pituitary-gonadal axis. The [D-Lys3]-Growth Hormone Releasing Peptide-6 ([D-Lys3]-GHRP-6) is a ghrelin antagonist that acts on ghrelin receptors (GHS-R1). The objective of this study was to evaluate the effect of [D-Lys3]-GHRP-6 on reproduction variables in feed restricted ewes. Two experiments were conducted. Experiment I was conducted for 30 days; and Experiment II for 13 days. In both experiments the ewes (n = 18) were randomly assigned to: Control (CO): fed to meet maintenance requirements; Feed restriction (FR): 80% of maintenance restriction; or Ghrelin antagonist (GA): feed restricted and daily subcutaneous of 7.5μg/kg of [D-Lys3]-GHRP-6. Plasma was collected to measure hormones and metabolite concentration. In Experiment II, the hypothalamus and ovaries were collected on day 13. In both Experiments, sheep allocated to the FR and GA treatments decreased their body weight compared with sheep in the CO group (P 0.10). Experiment I: Plasma ghrelin concentration was greater (P < 0.01) in FR and GA compared with CO ewes. Plasma non-esterified fatty acids concentration was greater (P < 0.01) in GA and FR than CO. Experiment II: Kisspeptin1-Receptor (Kiss1-R) mRNA expression was greater in FR (P < 0.01) and tended to be greater in GA (P = 0.10) compared with CO ewes. The neuro peptide-Y (NPY) mRNA expression was greater (P = 0.03) in FR than CO; and tended to be greater (P = 0.06) compared with GA ewes. Growth hormone releasing hormone (GhRH) mRNA expression was greater in GA (P = 0.04) and tended to be greater in FR (P = 0.07) compared with CO ewes. Feed restriction increased GhRH, NPY, and Kiss-R mRNA expression in hypothalamus without affecting reproductive variables.Ghrelin antagonist may prevent an increase inNPY expression in ewes.